From microscale redox cycling to urban dust: A three-stage Cu isotope fractionation model for arid tailings and the role in tracing Cu in street dust - Verónica Moreno-Rodríguez; Rafael Del Rio-Salas; Ryan Mathur; Narda Hayram Serrano-Bojorquez; René Loredo-Portales; Sergio Adrián Salgado-Souto; Lily Moore; Cameron Lasinsky; Eduardo Villalobos-Portillo (Environmental Pollution, 2026)

Molybdenum isotope fractionation in Collision-type magmatic-hydrothermal systems: evidence from the Leimengou porphyry Mo deposit - Nan Qi; Anthony E. Williams-Jones; YunPeng Dong; Ryan Mathur; XinKai Chen; YanJing Chen (Mineralium Deposita, 2026)

Extensive titanium isotope fractionation in magmatic and hydrothermal mineral systems - Christopher Emproto; Ryan Mathur; Adam C. Simon; Linda Godfrey; Jeffrey D. Vervoort; Mingguang Sun; Courteney Dhnaram; Vladimir Lisitsin; Martin Reich; Fernando Barra (Chemical Geology, 2026)

Silver is immobile in Ag-rich mine waste: Isotopic evidence from anthropogenic soils - Maria Vaňková; Aleš Vaněk; Anastasiia Shalabai; Martin Mihaljevič; Vojtěch Ettler; Martin Racek; Petr Drahota; Petr Fleissig; Petra Vokurková; Tereza Zádorová; Vít Penížek; Tomáš Hrdlička; et al. (Journal of Geochemical Exploration, 2026)

Province-scale tin and zinc stable isotope fractionation trends in the Bolivian tin belt - Evan C. Hirsh; Adam C. Simon; Ryan Mathur; Wayne Powell; Peter Megaw; Dan Asael (Geochimica et Cosmochimica Acta, 2026)

Cu isotopes resolve acid mine drainage sources and treatment pathways at the argo tunnel water treatment plant - Molly C. Morgan; Ryan Mathur; Elizabeth A. Holley; Cameron Lasinsky (Chemical Geology, 2026)

Timing of the telescoped sediment-hosted Cu-(Ni) and Pb-Zn-Ba mineralization at the Oumjrane vein system (Eastern Anti-Atlas, Morocco) and its relevance to Pre-Cretaceous Central Atlantic and Maghrebian Tethys geodynamics - Mohamed Idbaroud; Mohammed Bouabdellah; Gilles Levresse; E.L. Mostafa Mouguina; Ryan Mathur; Erik Melchiorre; Johan Yans; Ahmed El Guedou (Gondwana Research, 2026)

The sulfur isotope evolution of the Duobuza Cu-Au porphyry deposit in the Duolong district, Central Tibet, China - Jia Sun; Jingwen Mao; Georges Beaudoin; Ryan Mathur; Xianzhe Duan; Yubin Li (Mineralium Deposita, 2025)

Coupled antimony and sulfur isotopic composition of stibnite as a window to the origin of Sb mineralization in epithermal systems (examples from the Kremnica and Zlatá Baňa deposits, Slovakia) - Peter Koděra; Ryan Mathur; Degao Zhai; Rastislav Milovský; Pavel Bačo; Juraj Majzlan (Mineralium Deposita, 2025)
Stibnite is a relatively common mineral in epithermal deposits, with little known about Sb transport and efficient stibnite precipitation. The famous Kremnica Au-Ag low-sulfidation deposit and Zlatá Baňa intermediate-sulfidation Pb-Zn-Cu-Au-Ag-Sb deposit are hosted in two different Neogene volcanic fields in Western Carpathians, Slovakia. In both deposits, stibnite-rich veins occur outside of major vein structures, accompanied by illite, illite/smectite, and kaolinite alteration, and affiliated to late-stage fluids (< 2 wt% NaCl eq., < 150 °C). Sulfur isotopic composition of stibnite and sulfides is different at both deposits, likely due to a different magmatic-hydrothermal evolution of the parental magmatic chambers in the Central and Eastern Slovak Volcanic Fields. The Sb isotopes (δ 123 Sb), however, show similar values and trends of gradual simultaneous increase with δ 34 S values, explained by a progressive precipitation of stibnite and its fractionation with the fluid. The data were modeled by two coupled Rayleigh fractionation models, (for Sb and for S), assuming a predominant Sb transport in HSb 2 S 4 – with a variable amount of S species. Higher molality ratio m S /m Sb of fluids was found in Kremnica (~ 3–4) than in Zlatá Baňa (~ 2). At both deposits, the heaviest δ 123 Sb values are accompanied by a decrease in the δ 34 S values probably due to the commencement of pyrite/marcasite precipitation. According to thermodynamic models of solubility of Sb(III) complexes and observations from active geothermal fields, stibnite precipitation was triggered by temperature decrease accompanied by mixing with a mildly acidic fluid (pH 4–5) of a steam-heated CO 2 -rich condensate on margins and in the final stages of epithermal systems. The proposed model for the origin of stibnite-bearing veins in epithermal systems can be used for their better targeting and efficient mineral exploration.

Fluid-mineral titanium isotope fractionation: Computational and empirical results with implications for mineral deposits - Christopher Emproto; Ryan Mathur; Mingguang Sun; Adam C. Simon; Linda Godfrey (Geochimica et Cosmochimica Acta, 2025)

Copper isotopic evidence of microbial gold fixation in the Mesoarchean Witwatersrand Basin - Ryan Mathur; Linda Godfrey; Hartwig E. Frimmel; Nathan Yee; David Mossman; Peter Baran; Victor A. Valencia (Geochimica et Cosmochimica Acta, 2025)

Bio-mediated enhancement of supergene copper mineralization: Evidence from Cu isotope geochemistry - J. Javier Rey-Samper; Ryan Mathur; Fernando Tornos (Geochimica et Cosmochimica Acta, 2025)

Water-rock interaction and magmatic contribution in thermal fluids of the Southern Volcanic Zone, Chile: Insights from Li, B and Sr isotopes - Sebastian Rivas; Pablo Sanchez-Alfaro; Fernanda Alvarez-Amado; Alida Perez-Fodich; Linda Godfrey; Pablo Becerra; Daniele Tardani; Pamela Perez-Flores; Felipe Aron; Catalina Fica; Carolina Munoz-Saez; Ryan Mathur (Journal of Volcanology and Geothermal Research, 2024)

Isotope evidence for the enrichment mechanism of molybdenum in methane-seep sediments: Implications for past seepage intensity - Meng Jin; Fang Chen; Niu Li; Jörn Peckmann; Ryan Mathur; Linda Godfrey; Duofu Chen (Geochimica et Cosmochimica Acta, 2024)

Geochemical evolution of the REE-enriched Cave Peak porphyry Mo-deposit, Trans-Pecos Texas, USA - Mert Ugurhan; Brent Alan Elliott; J. Richard Kyle; Daniel F. Stockli; Ryan Mathur (Lithos, 2024)

Corrigendum to “Compositional variation and Sn isotope fractionation of cassiterite during magmatic-hydrothermal processes” [Earth Planet. Sci. Lett. 613 (2023) 118,186] - Jinghua Wu; Huan Li; Ryan Mathur; Audrey Bouvier; Wayne Powell; Kotaro Yonezu; Dapeng Zhu (Earth and Planetary Science Letters, 2024)

Silver isotopes: A tool to trace smelter-derived contamination - Aleš Vaněk; Maria Vaňková; Martin Mihaljevič; Vojtěch Ettler; Petr Drahota; Lenka Vondrovicová; Petra Vokurková; Ivana Galušková; Tereza Zádorová; Ryan Mathur (Environmental Pollution, 2023)

Fluid inclusion and H–O-S-Pb isotope constraints on the origin of carbonate-hosted Hg-Sb mineralization at Gongguan, central China - Gang Zhao; Degao Zhai; Jiajun Liu; Ryan Mathur (Mineralium Deposita, 2023)

Compositional variation and Sn isotope fractionation of cassiterite during magmatic-hydrothermal processes - Jinghua Wu; Huan Li; Ryan Mathur; Audrey Bouvier; Wayne Powell; Kotaro Yonezu; Dapeng Zhu (Earth and Planetary Science Letters, 2023)

Constraints on ore-forming fluid evolution and guidance for ore exploration in the Zhaxikang Sb–Pb–Zn–Ag deposit in southern Tibet: insights from silver isotope fractionation of galena - Da Wang; Ryan Mathur; Youye Zheng; Hongjie Wu; Yiwen Lv; Gangyang Zhang; Ren Huan; Miao Yu; Yujie Li (Mineralium Deposita, 2022)

Fluid mixing leads to main-stage cassiterite precipitation at the Xiling Sn polymetallic deposit, SE China: evidence from fluid inclusions and multiple stable isotopes (H–O–S) - Peng Liu; Jingwen Mao; Wei Jian; Ryan Mathur (Mineralium Deposita, 2020)

Evidence of genetic erosion in a peripheral population of a North American game bird: the Montezuma quail (Cyrtonyx montezumae) - Samarth Mathur; John M. Tomeček; Ashlyn Heniff; Ryan Luna; J. Andrew DeWoody (Conservation Genetics, 2019)

Geochemical, mineralogical and Re-Os isotopic constraints on the origin of Tethyan oceanic mantle and crustal rocks from the Central Pontides, northern Turkey - Ömer Faruk Çelik; Andrea Marzoli; Robert Marschik; Massimo Chiaradia; Ryan Mathur (Mineralogy and Petrology, 2018)

Constraining the timing of porphyry mineralization in northwest Iran in relation to Lesser Caucasus and Central Iran; Re–Os age data for Sungun porphyry Cu–Mo deposit - Vartan Simmonds; Mohssen Moazzen; Ryan Mathur (International Geology Review, 2017)

New isotopic evidence bearing on bonanza (Au-Ag) epithermal ore-forming processes - James A. Saunders; Ryan Mathur; George D. Kamenov; Toru Shimizu; Matthew E. Brueseke (Mineralium Deposita, 2016)

Mo isotope fractionation during hydrothermal evolution of porphyry Cu systems - Behnam Shafiei; GholamHossein Shamanian; Ryan Mathur; Hassan Mirnejad (Mineralium Deposita, 2015)

Erratum to: Re–Os isotope evidence for mixed source components in carbonate-replacement Pb–Zn–Ag deposits in the Lavrion district, Attica, Greece - Paul G. Spry; Ryan D. Mathur; Todd A. Bonsall; Panagiotis Ch. Voudouris; Vasilios Melfos (Mineralogy and Petrology, 2014)

Re–Os isotope evidence for mixed source components in carbonate-replacement Pb–Zn–Ag deposits in the Lavrion district, Attica, Greece - Paul G. Spry; Ryan D. Mathur; Todd A. Bonsall; Panagiotis Ch. Voudouris; Vasilios Melfos (Mineralogy and Petrology, 2014)

Use of Cu isotopes to distinguish primary and secondary Cu mineralization in the Cañariaco Norte porphyry copper deposit, Northern Peru - Ryan Mathur; Joaquin Ruiz; Michael J. Casselman; Peter Megaw; Robert van Egmond (Mineralium Deposita, 2012)

Variation of Mo isotopes from molybdenite in high-temperature hydrothermal ore deposits - Ryan Mathur; S. Brantley; A. Anbar; F. Munizaga; V. Maksaev; R. Newberry; J. Vervoort; G. Hart (Mineralium Deposita, 2010)

Late Archean Cu-Au-Mo mineralization at Gameleira and Serra Verde, Carajs Mineral Province, Brazil: constraints from Re-Os molybdenite ages - Robert Marschik; Ryan Mathur; Joaquin Ruiz; Richard A. Leveille; Antonio-Jos de Almeida (Mineralium Deposita, 2005)

A Re–Os study of sulfide minerals from the Bagdad porphyry Cu–Mo deposit, northern Arizona, USA - Fernando Barra; Joaquin Ruiz; Ryan Mathur; Spencer Titley (Mineralium Deposita, 2003)